Efficacy of zofenopril in combination with thiazide diuretics in patients with acute myocardial infarction: a pooled individual data analysis of four randomized, double-blind, controlled, prospective studies - Borghi C; Omboni S; Reggiardo G; Bacchelli S; Degli Esposti D; Ambrosioni E (Dove Medical Press, 2018)
Claudio Borghi,1 Stefano Omboni,2 Giorgio Reggiardo,3 Stefano Bacchelli,1 Daniela Degli Esposti,1 Ettore Ambrosioni1 On behalf of the SMILE Working Project 1Unit of Internal Medicine, Policlinico S. Orsola, University of Bologna, Bologna, Italy; 2Clinical Research Unit, Italian Institute of Telemedicine, Varese, Italy; 3Mediservice S.r.l., Agrate Brianza, Italy Background: In the Survival of Myocardial Infarction Long-Term Evaluation (SMILE) studies, early administration of zofenopril after acute myocardial infarction (AMI) was prognostically beneficial as compared to placebo and other angiotensin-converting enzyme inhibitors (ACEIs), such as lisinopril and ramipril. Here, we investigated whether zofenopril efficacy could be affected by a concomitant use of thiazide diuretics (TDs). Methods: This was a post hoc analysis of pooled individual patient data from the SMILE studies. Patients treated with other diuretics than TDs were excluded. The primary study endpoint was the 1-year combined occurrence of death or hospitalization for CV causes, with or without TD. Results: Among 2,995 patients, 263 (8.8%) were treated with a combination including a TD (TD+), whereas 2,732 (91.2%) were not treated with any diuretic (TD-). Proportions of subjects who were treated with TD were equally distributed (p=0.774) within the placebo, zofenopril, and other ACEIs groups. The 1-year risk of major cardiovascular events was similar in TD+ (18.3%) and TD- (16.8%) patients (hazard ratio [HR] 1.04; 95% CI 0.74–1.45; p=0.838). After stratifying per concomitant treatment and TD, the 1-year risk of CV events was significantly lower with zofenopril than with placebo (HR 0.70; 95% CI 0.55–0.88; p=0.002) and other ACEIs (HR 0.58; 95% CI 0.46–0.74; p=0.0001). Treatment with ACEIs and TD as concomitant therapy was associated with a larger blood pressure (BP) reduction (p=0.0001 for systolic BP and p=0.045 for diastolic BP). Conclusion: In post AMI patients, zofenopril maintained its positive impact on prognosis compared to placebo or other ACEIs, regardless concomitant TD administration. In this setting, TD shows advantages in managing the most difficult hypertensive patients. Keywords: acute myocardial infarction, drug therapy, angiotensin-converting enzyme inhibitors, thiazide diuretics, cardiovascular risk